2017
DOI: 10.1037/fam0000330
|View full text |Cite
|
Sign up to set email alerts
|

Family dinner frequency interacts with dinnertime context in associations with child and parent BMI outcomes.

Abstract: For youth and parents, frequent family meals have been consistently associated with positive dietary outcomes but less consistently associated with lower body mass index (BMI). Researchers have speculated dinnertime context (dinnertime routines, parent dinnertime media use) may interact with family meal frequency to impact associations with BMI. The present study evaluates the associations and interactions between dinnertime context measures and family dinner frequency with parent and child BMI. This cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…child age, sex, parental college education, race and qualifying for free/reduced cost lunch; ). Similarly, Horning and colleagues examined family mealtime routines, including the frequency and predictability of family mealtimes, in 160 US children (ages 8–12) and found that more predictable dinnertime routines were inversely related to zBMI, even after controlling for demographic variables (i.e. race and economic assistance).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…child age, sex, parental college education, race and qualifying for free/reduced cost lunch; ). Similarly, Horning and colleagues examined family mealtime routines, including the frequency and predictability of family mealtimes, in 160 US children (ages 8–12) and found that more predictable dinnertime routines were inversely related to zBMI, even after controlling for demographic variables (i.e. race and economic assistance).…”
Section: Resultsmentioning
confidence: 99%
“…Studies also examined the broad home environment and household crowding . Lumeng and colleagues used the full 55‐item Home Observation for Measurement of the Environment (HOME)‐Middle Childhood scale and found that the home environments of normal weight children were rated to be of a higher overall quality than those of overweight or obese children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical aspects of mealtime environment have been explored most in relation to mealtime television use, linked to child overweight in a recent metaanalysis [10]. Possible mechanisms include exposure to obesogenic food advertising (which can have both immediate effects on dietary intake, and longer term effects on fast food preferences [11,12]); adverse effects of mealtime screen use on appetite regulation and control [13]; and less parental monitoring of food consumption [14]. The social and physical context of mealtimes may have independent and/or interactive effects on children's diet, although it is not clear whether mealtime screen use compromises or promotes a positive atmosphere [15,16].…”
Section: Family Mealtime Environmentmentioning
confidence: 99%